Қарақалпақ тилинде диалектлик вариантлар (ILIM hám JÁMIYET, 2026)
The article discusses dialectal words and the issue of variation. The use of phonetic and phonetic-lexical variants of dialectal words is analyzed based on the materials of the northern dialect.